French Public Finances : Modeling Long-Term Prospects and Reform Options - Habermeier, Karl (IMF Working Papers; Working Paper ;, 1998)
Over the coming decades, demographic developments will lead to a significant increase in public outlays on pensions and health care, relative to national income. This study extends earlier work by considering the adverse effects of taxation on the determinants of economic growth -- in particular, investment, productivity growth, and labor force participation. Available empirical evidence suggests that these adverse effects could well be sizable, and that conventional estimates of the adverse effects of population aging probably severely underestimate their impact on the public finances and economic performance. The paper uses stochastic simulations to examine the robustness of the results to changes in parameter values. It also provides quantitative simulations of various reform options, including mainly an increase in the effective retirement age and flanking labor market measures.